2013
DOI: 10.9775/kvfd.2012.7244
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Levels Total Antioxidant and Oxidant Capacity in Cattle with Foot and Mouth Disease

Abstract: The aim of this study was to investigate total antioxidant (TAC), oxidant capacity (TOC) and nitric oxide levels (NO) in cattle with foot-and-mouth-diseases (FMD). Twenty Swiss Brown cattle aged between 24 and 48 months were used. Animals were divided into two groups as control (n=10) and FMD (n=10). Blood samples were collected from jugular vein and centrifuged. TOC and NO levels were found to be significantly higher in FMD group compared to those of control group. However, no significant differences were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…A study conducted by Bozukluhan et al [9] found that serum NO levels in healthy animals (control group) were lower than those of diseased animals. In our study, the PRID was administered to healthy animals and because the device caused stress to the animal, we found that NO levels rose after the procedure.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A study conducted by Bozukluhan et al [9] found that serum NO levels in healthy animals (control group) were lower than those of diseased animals. In our study, the PRID was administered to healthy animals and because the device caused stress to the animal, we found that NO levels rose after the procedure.…”
Section: Discussionmentioning
confidence: 96%
“…Nitric oxide (NO) plays a role in many of the body's physiological functions and is produced by nitric oxide synthesis. NO is mostly produced by macrophage, neutrophil and mast cells [2,8,9] . Studies performed on cattle have reported that OS factors increase when the animals become sick [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that NO plays an important role in the primary defense mechanism against several pathogens; bacteria, viruses and parasites and NO production to be induced by various viruses which inhibit virus replication in vivo and [35][36][37] . Increased NO, a gaseous free radical, in this study is in agreement with the study of cellular elements such as lipopolysaccharide and glycolipoprotein, have been reported to activate leukocytes and stimulate the production of pro-inflammatory cytokines which induces production of NO through activation of inducible nitric oxide synthase (iNOS) [38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies in our laboratory and others, it has been reported that the amount of NO can change in response to various toxicity conditions [12][13][14][15][16][17][18] which are closely associated with animal and human disease conditions. In this chapter, we mention NO 3 − and NO 2 − , the molecules which are naturally found in foods as NO sources, agricultural activities such as the use of artificial fertilizers, polluted water, curing process to give a natural smell and taste to meat.…”
Section: Introductionmentioning
confidence: 99%